Metaphenotypes associated with recurrent genomic lineages of Campylobacter jejuni responsible for human infections in Luxembourg - Nennig, Morgane; Clément, Arnaud; Longueval, Emmanuelle; Bernardi, Thierry; Ragimbeau, Catherine; Tresse, Odile (Frontiers in Microbiology, 2022)
Campylobacter jejuni is a leading cause of foodborne illnesses worldwide. Although considered fragile, this microaerophilic bacterium is able to survive in various challenging environments, which subsequently constitutes multiple sources of transmission for human infection. To test the assumption of acquiring specific features for adaptation and survival, we established a workflow of phenotypic tests related to the survival and the persistence of recurrent and sporadic strains. A representative collection of 83 strains isolated over 13 years from human, mammal, poultry, and environmental sources in Luxembourg, representing different spreading patterns (endemic, epidemic and sporadic), was screened for survival to oxidative stresses, for acclimating to aerobic conditions, and for persistence on abiotic surfaces. Using the cgMLST Oxford typing scheme for WGS data, the collection was classified into genomic lineages corresponding to host-generalist strains (lineages A and D, CC ST-21), host-specific strains (lineage B, CC ST-257 and lineage C, CC ST-464) and sporadic strains. We established that when a strain survives concentrations beyond 0.25 mM superoxide stress, it is six times more likely to survive hyperoxide stress and that a highly adherent strain is 14 times more likely to develop a biofilm. Surprisingly, more than half of the strains could acclimate to aerobic conditions but this capacity does not explain the difference between recurrent genomic lineages and sporadic strains, neither the survival to oxidative stresses, while recurrent strains have a significantly higher adhesion/biofilm formation capacity than sporadic ones. From this work, the genomic lineages with more stable genomes could be characterized by a specific combination of phenotypes, called metaphenotypes. From the functional genomic analyses, the presence of a potentially functional T6SS in the strains of lineage D might explain the propensity of these strains to be strong biofilm producers. Our findings support the hypothesis that phenotypical abilities contribute to the spatio-temporal adaptation and survival of stable genomic lineages. It suggests a selection of better-adapted and persistent strains in challenging stress environments, which could explain the prevalence of these lineages in human infections.